An Analysis of Twitter (X) as a Media for Learning English: Users’ Perceptions and Experiences - Siti Kholifah Isnaini; Ahmad Madkur (Journal of English Development, 2026)
This study is to investigates students’ perceptions and experiences of using Twitter as a social media platforms for learning English, with ta focus on the development of reading and speaking skills, vocabulary enrichment, and grammatical awareness. The study employed a qualitative case study design involving students from various semesters in the English Department. Data were collected through semi-structured interviews and were analyzed thematically. The findings revealed that students have positive perceptions of using Twitter for English learning. They reported that Twitter facilitates access to authentic English content, supports vocabulary development, encourages interaction with other users, and contributes to the improvement of overall English language skills. However, the study also identifies several challenges experienced by students, including difficulties in understanding unfamiliar slang and complex expressions, limited feedback on language use, confusion in navigating certain features, exposure to unscreened content, and issues related to mispronunciation. These findings indicate that Twitter can serve as a supportive tool for English language learning. However, appropriate guidance and critical use are necessary to maximize its benefits and minimize potential challenges.